THE EFFECTIVENESS OF MNEMONIC DEVICES IN LEARNING NEW VOCABULARY: REEVALUATING STANDARDIZED TESTING - Bayjanov Saparniyaz (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This study investigates the role of mnemonic devices in enhancing vocabulary acquisition while critically examining the implications of standardized testing on language learning outcomes. By integrating cognitive psychology with educational measurement theories, the study explores how mnemonic techniques—such as keyword, imagery, and pegword strategies—affect vocabulary retention compared to traditional learning and testing methods. Data were collected from a sample of university students who were assessed using both immediate recall tests and standardized testing formats. Results indicate that mnemonic devices significantly improve retention and learning satisfaction, suggesting that standardized tests may undervalue the benefits of cognitive strategies in vocabulary learning (Johnson, Mnemonic Memory: Techniques and Strategies, p. 112). Implications for curriculum design and assessment practices are discussed.